Ugandan Borders: Theatre of Life and Death. Issue 3 (3rd July 2018) - Ng, Kean C. K.
ABSTRACT: This article analyzes the resilience of informal cross-border trade among the Bakiga people, living in the Kabale region. It argues that the state and its borders do not only frame economic realities, but are an intrinsic, at times inconvenient and at times profitable, part of cosmology of life on the border. Ugandan border-dwellers and traders are mostly not resisting the state, but living with and using the "system" as best as they can. The state is not always a foreign hegemon, but a frame of life.